The effect of virtualization of organizational performance on organizational stability through the synergy of human capital and organizational wisdom organization in sports organizations - Javidi, Noushin; Mohammadzadeh, Younes (Technium Sustainability, 2022)
This study aimed to investigate the effect of virtualization of organizational performance on organizational sustainability with the mediating role of the synergy of human resources and organizational wisdom. The type of research is applied in terms of purpose and descriptive survey in terms of implementation. The statistical population of this study consisted of all employees of the Municipal Sports Organization N=480 and also the statistical sample of the study was selected using Morgan sampling table and stratified randomly from the Municipal Sports Organization n= 215. To collect data from one personal information questionnaire and four questionnaires of organizational virtualization (William Stride, 2007), organizational wisdom-questionnaire (Brown and Green, 2006) and human capital synergy questionnaire (Ahmadi et al., 2017), and organizational sustainability questionnaire ( Dick et al., 2012) were used. The validity of these questionnaires was confirmed by seven professors of sports management of Islamic Azad University, Arsanjan Branch, and also the reliability of the questionnaires was 0.92, 0.87, 0.94, and 0.89 using Cronbach’s alpha test, respectively. In this research, to analyze the collected data, first, the questionnaire questions are described at the descriptive level using statistical indicators and then at the inferential level to examine the accuracy of the hypotheses and the relationships between the research variables of the technique. Path analysis was used using Smart PLS software version 3. The most important results of the study indicated that the virtualization of organizational performance has a significant effect on organizational stability with the mediating role of synergy of human resources and organizational wisdom.